2016
DOI: 10.5262/tndt.2016.1001.20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Young Age Group’s Thoughts and Knowledge Levels on Organ Donation in Terms of Education Given

Abstract: ÖZAMAÇ: Çalışma lise öğrencilerinin organ bağışına yönelik düşünce ve bilgi düzeylerinin belirlenmesi, ayrıca verilen eğitime göre düşüncelerinde ve bilgi düzeylerinde anlamlı farklılık oluşup, oluşmadığının incelenmesi amacıyla yapılmıştır. GEREÇ ve YÖNTEMLER:Araştırma Ankara ilinde eğitim veren bir kız meslek lisesi 9. sınıf öğrencilerinde uygulanmıştır. Çalışmaya 113 öğrenci katılmıştır. Veriler anket yöntemi ile toplanmıştır. Öğrencilere ön test uygulanmasının ardından, 60 dakika süren eğitim verilerek son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Abbasi et al (2018) reported that most of the participants required religious support to be able to donate organs (Abbasi et al, 2018). In Uzuntarla's (2016) study in which he provided training on organ transplantation and donation, the rate of those who believed that there was no religious objection increased from 24.8% prior to the training to 80.5% post training (Uzuntarla, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Abbasi et al (2018) reported that most of the participants required religious support to be able to donate organs (Abbasi et al, 2018). In Uzuntarla's (2016) study in which he provided training on organ transplantation and donation, the rate of those who believed that there was no religious objection increased from 24.8% prior to the training to 80.5% post training (Uzuntarla, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are similar results in the studies [31,32] conducted in Malaysia and Hong Kong, respectively. There are research results that training increases knowledge and awareness, and increases self-efficacy [33,34]. In [35], it was stated that the trainings on the first-aid should be repeated at certain intervals, otherwise the information is forgotten, and it reduces the first-aid selfefficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Kocak et al [20] reported that medical faculty students know what to do when donating organs, but they will donate their organs only when a family member needs them. Uzuntarla et al [21], in as survey of 113 vocational high school students, stated that education largely eliminated the students' lack of knowledge about organ donation. Fuel et al [22] stated that most of the health services vocational school students were keen on organ donation, but 61.2% did not know the conditions required for donation.…”
Section: Discussionmentioning
confidence: 99%